(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The inland fisheries and aquaculture of Bangladesh and Nigeria were critically examined with a view to comparing their fish production and farming systems, nature of seed supply, contribution to country’s Gross Domestic Product (GDP) and the transferability of experiences towards development of the fisheries sector. A review-based study was conducted based on the available information in journals articles, reports, Bangladesh and Nigeria Departments of Fisheries Statistical Year Books, text books, thesis and web documents. There are considerable similarities between Bangladesh and Nigeria in terms of geographical position, agro-ecology, fisheries resources and the socio-economic condition, fish eating tradition and domestic demand for fish consumption of the people. Bangladesh aquaculture systems though mainly semi-intensive but more developed than that of Nigeria in terms of fish seed and feed supply while Nigeria, though adopts the intensive culture technique but experiences lower production and higher import of fish. From the findings of this review, it could be argued that Bangladesh needs to fully harness its abundant resources such as seeds, ponds, water, so as to achieve self-sufficiency in fish supply and develop export market. Alternatively, Nigeria needs to adopt, diversify and invest more in aquaculture and fisheries receiving learning from an aquaculture growing country, like Bangladesh, so as to increase production and reduce import. J. Bangladesh Agril. Univ. 16(3): 523–532, December 2018